Trends and Outcomes in Reporting and Grading Complications of Urological Surgery: A Retrospective Analysis - Rehman, Habib Ur; Muhammad Asif; Hussain Patujo, Yassar; Amjad, Maliha; Khan, Hamza; Safiullah, Tahmeedah; Wakeel, Muhammad Inzamam; Ahmad, Irshad (Indus Journal of Bioscience Research, 2024)
Introduction: Complications in urological surgery can range from minor, self-limiting issues to severe, life-threatening events requiring significant medical intervention. This study aimed to assess the reporting and grading of complications in urological surgery, focusing on current trends and future perspectives. Methodology: Conducted at the Institute of Kidney Diseases, Peshawar, from 2022–2023. This retrospective study included 165 patients diagnosed with vesicovaginal fistula (VVF) or bladder urethral stricture and hypoplasia (BURSH) requiring surgical intervention. Patients with prior surgeries that could interfere with complication assessment or incomplete medical records were excluded. Results: Various surgical procedures were performed, tailored to the individual’s medical history, fistula location, and size. Surgical approaches included transvaginal repair, transabdominal repair, or laparoscopic repair. The mean age of patients was 49.23 years (range 26–74), with 90% females and 10% males. Comorbidities included diabetes (20%), hypertension (25%), and other chronic illnesses (15%), with an average BMI of 24. A history of smoking and alcohol consumption was reported in 15% and 10% of patients, respectively, while 30% had undergone prior urological surgeries. Discussion: Post-surgery, 70% achieved satisfactory urinary control, 20% experienced mild to moderate incontinence, and 10% reported persistent control issues. Minimal to moderate pain was noted in 60%, while 25% experienced transient discomfort resolving within three months, and 15% reported chronic pain. Conclusion: The findings highlight the importance of personalized surgical approaches, with minimally invasive techniques reducing complication rates and improving outcomes in urological surgeries for VVF and BURSH.